KNOWLEDGE MANAGEMENT: SEBUAH STRATEGI PENGEMBANGAN SUMBER DAYA MANUSIA DALAM KONTEKS PENDIDIKAN AGAMA KRISTEN MENGHADAPI ERA POSTHUMAN - Febriani Upa (Didaskalia: Jurnal Pendidikan Agama Kristen, 2023)
The industrial era 5.0 has had many impacts on human civilization. One of them is the emergence of posthumans where human life is in contact with advances in science and technology. This certainly has an impact on human life, has a positive impact when technology is used to facilitate human work, but it can also have a negative effect when technology controls and controls humans. Therefore, human efforts are needed to develop their potential so that they can face and balance the challenges in the posthuman era in the future. Knowledge Management is a strategy that can help humans manage knowledge (self-potential and technology) that can be implemented in Christian Religious Education